2014
DOI: 10.1093/hmg/ddu478
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study in Chinese identifies novel loci for blood pressure and hypertension

Abstract: Hypertension is a common disorder and the leading risk factor for cardiovascular disease and premature deaths worldwide. Genome-wide association studies (GWASs) in the European population have identified multiple chromosomal regions associated with blood pressure, and the identified loci altogether explain only a small fraction of the variance for blood pressure. The differences in environmental exposures and genetic background between Chinese and European populations might suggest potential different pathways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
121
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 175 publications
(130 citation statements)
references
References 35 publications
8
121
0
1
Order By: Relevance
“…Ten SNPs have been associated with SBP or DBP with GWAS significance in East Asian, 4 and we also identified and replicated 19 BP loci in Chinese population. 12 We pruned these SNPs and identified 22 uncorrelated (r 2 <0.5) SNPs. Of these SNPs, 2 (rs10745332 and rs17030613) were in MOV10 but showed weak linkage disequilibrium (r 2 =0.19 HapMap CHB+CEU).…”
Section: Snps Selection Genotyping and Grsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten SNPs have been associated with SBP or DBP with GWAS significance in East Asian, 4 and we also identified and replicated 19 BP loci in Chinese population. 12 We pruned these SNPs and identified 22 uncorrelated (r 2 <0.5) SNPs. Of these SNPs, 2 (rs10745332 and rs17030613) were in MOV10 but showed weak linkage disequilibrium (r 2 =0.19 HapMap CHB+CEU).…”
Section: Snps Selection Genotyping and Grsmentioning
confidence: 99%
“…For example, at least 6 common variants identified in Europeans were monomorphic or had low minor allele frequency (<0.05) in the Chinese population, 12 suggesting genetic heterogeneity between different ethnic populations. Kato et al 4 published the first large-scale GWAS meta-analysis for BP in East Asians.…”
mentioning
confidence: 99%
“…The evolutionary role of Casz1 in heart development is further emphasized by genome-wide association studies showing genetic association of the CASZ1 locus with blood pressure and hypertension (Levy et al, 2009;Takeuchi et al, 2010;Lu et al, 2015). Consistently, it has been demonstrated that CASZ1 has an essential role in blood vessel assembly and lumen formation (Charpentier et al, 2013a,b).…”
Section: Introductionmentioning
confidence: 94%
“…Unfortunately, the genotyped individuals in original GWAS of Chinese hypertensive populations 38,39 were relatively small, which may not be sufficient to discover the association of LPAR1 with hypertension when P value cutoff was set as GWAS significance (<10 -7 ). Although some meta-analysis 35,40,41 in East Asian increased sample size by combining various experiments, it can be strongly disturbed by the experimental similarity and validity. These disturbances, together with strict P cutoff, may lead to ignorance of those who have mild effects on trait.…”
mentioning
confidence: 99%
“…[32][33][34][35][36][37][38][39][40][41] However, LPAR1 has not been reported by these GWAS. It was probably because the results of GWAS can be affected by several factors, such as population size, stratification, conservative statistic cutoff, and chip density.…”
mentioning
confidence: 99%